A plithogenic statistical approach to digital security measures and emotional health in childhood and adolescence - Carlos Hurtado; Marco Villa; Lady Raquel Caicedo Sandoval; Isea Josia (Journal of Fuzzy Extension and Applications)
The rapid digitalization of society has raised important concerns regarding the psychological and emotional well-being of minors navigating online environments. This study aims to analyze the relationship between digital security measures and the psychological resilience, self-esteem, and social interactions of children and adolescents. Utilizing a plithogenic statistical approach, which accounts for the complex, indeterminate nature of these variables, this study examined how various dimensions of digital security—including confidentiality, integrity, authentication, and access control—impact key aspects of minors' emotional well-being. Analysis of expert evaluations revealed that robust digital protections enhance emotional stability by reducing cyberbullying risks and fostering a supportive online environment, leading to higher self-esteem and healthier interpersonal relationships. These findings underscore the necessity for comprehensive educational programs that integrate both technical digital literacy and emotional management skills. Such programs can empower minors to navigate digital spaces securely and confidently, fostering overall psychological well-being in a digital age. Further research is recommended to expand on these findings and explore their applications across diverse socioeconomic contexts.